Public Perception of Laying Hen Fecal Waste in Tanete Village, Maritengngae District, Sidenreng Rappang Regency - Agustan Saini; Angga Nugraha; Nurul Purnomo; Muh. Irwan; Musdalifa Mansur; Armayani M. (Global Writing Academica Researching and Publishing, 2026)
This study aims to determine public perceptions of laying hen feces and the impacts felt by the community in Tanete Village, Maritengngae District, Sidenreng Rappang Regency. The study involved 36 respondents selected by purposive sampling from 203 residents living within a 500-meter radius of the farm. Data were collected through observation, interviews, and Likert-scale questionnaires, then analyzed using descriptive statistics. The results showed that public perception of laying hen feces was in the sufficient category (42%). The community is aware of the environmental impacts caused, but still accepts the existence of the farm because it provides economic benefits. The most perceived impacts include unpleasant odors (42%), disturbances in environmental cleanliness (47%), and an increase in the presence of flies (38%). In addition, waste also affects the comfort and daily activities of the community. In general, laying hen feces still cause environmental and social disturbances, so better waste management is needed to reduce the negative impacts felt by the community.